Bifurcation and chaotic vibration in electromechanical integrated toroidal drive. (June 2015) - Xu, Lizhong; Gao, Yanxia
In this paper, we analyze the nonlinear magnetic-interaction forces in an electromechanical integrated toroidal drive and deduce the nonlinear electromechanically coupled dynamics equations of the drive system. Based on these equations, the bifurcation and chaotic vibrations of the drive system are investigated. The results show that chaotic vibrations occur in the drive system when the current in worm coils is relatively large. The current in worm coils, the ratio of the center distance to planet radius, the worm-coil inductance, and the support stiffness of the planet all have significant influence on the nonlinear vibrations of the drive system. We show the ranges for the system parameters that lead to a drive system with good dynamics. These results can be used to predict the dynamic load in a drive system and are useful for maximizing the power density of a drive system.